Les sépultures mésolithiques de Téviec et Hoedic : révisions bioarchéologiques - Boulestin, Bruno (Archaeopress archaeology., 2016)
This work presents the long lacking bioarchaeological review study of the Teviec and Hoedic graves, located in Brittany and excavated from 1928 to 1934 by Marthe and Saint-Just Péquart.